SERVANT LEADERSHIP ALTERNATIVE LEADERSHIP MODEL AT UNIVERSITY - Goffar, Abdul (International Conference on Humanity Education and Society (ICHES), 2024)
One important component in institutional management in higher education is the role of the chancellor as an educational leader who is directly responsible for the entire academic process in higher education. The Chancellor as the key person in managing all campus residents has the biggest contribution to the overall success of the educational process at the university. This research aims to describe the leadership model (servant leadership) at the At-Taqwa Bondowoso Islamic College. This research method uses a qualitative approach with a phenomenological type. The data sources for this research are: Chair, deputy Chair, Lecturers, Education Personnel, and students with data collection techniques using observation, interviews and documentation. Descriptive data analysis techniques are carried out starting from data collection, data condensation, data presentation, and drawing conclusions/verification. The results of the research show that the servant leadership model that has been implemented by the Head of the At-Taqwa Bondowoso Islamic College is listening to the hopes of campus residents, empathizing, having and increasing self-awareness of campus residents, building persuasive power that unites togetherness among campus residents, having conceptualization and the ability to heal, the ability to serve the campus community, a commitment to individual development and a clear vision and mission for the future, and the ability to build a community. The servant leadership model can be an alternative as an appropriate model to be applied in managing higher education today, because this leadership model is in accordance with the educational philosophy in Indonesia, especially in educational development.